2018
DOI: 10.1103/physreve.97.052127
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Voronoi diagram based direction choices using uni- and bi-directional trajectory data

Abstract: In a crowd, individuals make different motion choices such as "moving to destination," "following another pedestrian," and "making a detour." For the sake of convenience, the three direction choices are respectively called destination direction, following direction, and detour direction in this paper. Here, it is found that the featured direction choices could be inspired by the shape characteristics of the Voronoi diagram. To be specific, in the Voronoi cell of a pedestrian, the direction to a Voronoi node is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
(41 reference statements)
0
13
0
Order By: Relevance
“…The results are so-called velocity-based models [14,73]. At the same time several more model types emerged: velocityobstacle-based models [22,4,13] for collision avoidance inspired by robotics, rule-based models such as [65,84] and models which combine different approaches like the optimal steps model (OSM) [68]. Most models have been adjusted and extended to fit the findings from interdisciplinary experiments and studies.…”
Section: Locomotion Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results are so-called velocity-based models [14,73]. At the same time several more model types emerged: velocityobstacle-based models [22,4,13] for collision avoidance inspired by robotics, rule-based models such as [65,84] and models which combine different approaches like the optimal steps model (OSM) [68]. Most models have been adjusted and extended to fit the findings from interdisciplinary experiments and studies.…”
Section: Locomotion Modelsmentioning
confidence: 99%
“…Several approaches for modeling microscopic pedestrian dynamics have been developed in the last decades [88]. Among these are models based on cellular automata (CA) [25,5,45,79,18,87], models based on ordinary differential equations (ODE) [34,9,8,14,73], models based on cognitive heuristics [65,84] and models based on optimizing a utility, such as the quasicontinuous optimal steps model [68,75,76,77].…”
Section: Introductionmentioning
confidence: 99%
“…One possible approach is to adopt the Voronoi diagrams which is a partitioning of a 2-D plane based on the “nearest-neighbor” rules ( Aurenhammer, 1991 ) assigning each dot to a corresponding cell. As a computational geometry method, Voronoi diagrams have been widely applied in various disciplines ( Fonseca et al, 2012 ; Lopes et al, 2017 ; Sun et al, 2018 ; Xiao et al, 2018 ). In civics and planning, Xiao et al (2018) used Voronoi diagrams to describe the pedestrian motion patterns wherein each pedestrian was represented by a point in a Voronoi cell.…”
Section: Introductionmentioning
confidence: 99%
“…As to the spatial map representation modeling, the visibility graph, [12][13][14] the Voronoi diagram, [15][16][17][18][19][20] and the navigation mesh [21][22][23][24] serve as the widely used map generation modeling method. In the visibility graph, the initial position, the goal position, and the vertices of obstacles in the simulation scenario are represented by the nodes.…”
Section: Introductionmentioning
confidence: 99%
“…And the walking direction of pedestrian in Voronoi cell can be divided into destination direction, potential detour direction, and potential following direction. 18 The three elementary walking directions are calculated inspired by the characteristics of the shapes of Voronoi cell. Sˇeda and Pich 19 have shown that generalized Voronoi diagrams can be used for fast generation of smooth paths sufficiently distant from obstacles.…”
Section: Introductionmentioning
confidence: 99%